Ukraine in the Contemporary Integration Processes: Preconditions and Problems - IHNATENKOТ.; PARKHOMENKO, V.; TARASENKOА. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
Given that the economic and social recovery of Ukraine is largerly conditional on its integration in the international economic system and effective involvement in the international division of labor, the article’s objective is to analyze preconditions and problems specific to the Ukraine’s integration in the global economic area. Intergration-specific aspects and problems in operation of the transport infrastructure and mining industry of Ukraine, strong and weak sides of Ukraine on the global energy market, the potentials of Ukraine in the agrarian sector are highlighted. It is emphasized that a priority mechanism for increasing the share of Ukraine’s trade on the European agrarian market is Free Trade Zone with EU, but a factor constraining growth in the agricultural exports of Ukraine to EU is failure of the most part of domestic producers to comply with technical, sanitary etc. terms for exporters to EU. The analysis covers statistical data on foreign trade of Ukraine in goods and services in 2016–2018, the commodity structure of Ukraine’s foreign trade in 2018, key indicators of the international trade of Ukraine in 2016–2018. It, above all, shows the negative balance of the Ukrainian foreign trade, which tendency is upward. The tradability index for the Ukrainian economy fell in this period from 81.0% до 79.9%, giving evidence of the decreasing participation of Ukraine in the international division of labor. The essential factors underlying the negative balance of foreign trade in goods are highlighted; measures to reduce the negative balance of foreign trade are proposed. The data showing the progress in Ukraine’s implementation of Association Agreement with EU are summed up. It is concluded that in spite of a series of steps towards the openness of Ukraine for the global market, the processes involved in the formation of the national foreign economic relations mechanism have been contradictory and ineffective. It calls for optimization of regulatory forms for foreign economic relations and implementation of a mechanism complying with the current terms of international economic relations.